(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The Middle East has always remained a significant geo-political, geo-strategic hotspot in world politics. For the past three centuries, the region has remained the centre of all important confrontations and a battleground for superpowers because of various aspects.